A look at the knowledge and percentage of vaccines related to human papillomavirus (HPV) in medical students at a private university center: A cross-sectional study (Research, Society and Development, 2022)
The objective of the present study was to evaluate the knowledge of medical students about human papillomavirus (HPV) infection, in addition to addressing knowledge about prevention and the rate of vaccine adepts. Cross-sectional study, through the application of an online questionnaire, which addressed the following aspects: technical and practical knowledge about HPV and its prophylaxis; vaccination rate of academics. The respective study had the participation of 139 medical students, 74.9% (n=103) were female and 25.9% (n=36) were male. In comparison between the sexes, women showed a greater participation to gynecology offices, as well as the discussion about STIs (p